2020
DOI: 10.3390/su12073019
|View full text |Cite
|
Sign up to set email alerts
|

The Nexus between Credit Channels and Farm Household Vulnerability to Poverty: Evidence from Rural China

Abstract: It is well known that finance is at the core of economic activities, and rural finance is an important force for agricultural development, rural economic growth, and farmer income growth, but how rural credit affects vulnerability to poverty of farm households is not yet known. The study on the nexus between the credit channels and vulnerability to poverty can not only realize targeted poverty alleviation but also promote sustainable rural development. This study measures vulnerability to poverty of Chinese fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 51 publications
1
14
0
Order By: Relevance
“…This means that the head of the poor farmer household who rec eives credit for agriculture will have the opportunity to move out of poverty. These results are consistent with previous studies by Addury (2019); Coulibaly & Yogo, (2016); Damayanti & Adam, (2015); Sun et al, (2020); Coulibaly & Yogo, (2016). However, although the impact of credit may reduce the probability of poor farmer households emerging from poor status, in fact, the coefficient value is very small.…”
Section: The Impact Of Credit On Farmers Household Efforts To Move Out Of Multidimensional Povertysupporting
confidence: 93%
See 2 more Smart Citations
“…This means that the head of the poor farmer household who rec eives credit for agriculture will have the opportunity to move out of poverty. These results are consistent with previous studies by Addury (2019); Coulibaly & Yogo, (2016); Damayanti & Adam, (2015); Sun et al, (2020); Coulibaly & Yogo, (2016). However, although the impact of credit may reduce the probability of poor farmer households emerging from poor status, in fact, the coefficient value is very small.…”
Section: The Impact Of Credit On Farmers Household Efforts To Move Out Of Multidimensional Povertysupporting
confidence: 93%
“…In addition, in developing an antipoverty policy in the agricultural sector, it is necessary to consider the movement of the Farmer Exchange Rate (NTP, NilaiTukar Petani), as it describes the indicators of farmer welfare. Credit assistance schemes, socio-economic conditions, asset ownership, arable land area, farmers would be more suitable if a po verty reduction program with direct cash assistance programs could directly benefit farmers (Coleman, 2000;Coulibaly & Yogo, 2016;Elsas & Krahnen, 2000;Fianto et al, 2018;Sun et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This implies that the marginal contribution of credit brings input levels closer to the optimal levels, thereby increasing production and output per head. Furthermore, access to credit is also considered to be an important tool for smoothing consumption, promoting production and reducing vulnerability to poverty especially for poor households (Dobridge, 2018; Thanh et al ., 2019; Sun et al ., 2020). Recently in Ghana, studies that have looked at access to credit and savings among smallholder farmers have been biased towards examining the determinants that influence smallholder access to credit and savings (see for example Asante-Addo et al , 2017; Sekyi et al ., 2019; Nordjo and Adjasi, 2019; Twumasi et al , 2019; Aidoo-Mensah, 2019).…”
Section: Literature Reviewmentioning
confidence: 99%
“…For instance, Fan and Xie (2014) examined the impact of public transfers on poverty vulnerability, and the results showed that public transfers had little influence on poverty vulnerability. Another study based on the China Household Finance Survey data (CHFS) found that bank credit had a positive impact on reducing poverty vulnerability-especially for farm households (Sun et al, 2020).…”
Section: Literature Reviewmentioning
confidence: 99%